Do Prices Affect Farmer’s Term of Trade in Indonesia? - Saad Murdy (School of Business, Bogor Agricultural University (SB-IPB), 2017)
This study aimed to identify the factors affecting the welfare of food crop farmers, measured by the food crop farmers’ terms of trade using the Vector Error Correction Model. The data used were monthly data from 2011 to 2016. The results of this study indicate that the medium-grain rice producer price and sharia financing provided by Sharia Banks in the agricultural sector contribute greatly to the welfare of the food crop farmers.Keywords: farmers’ terms of trade, food crops, sharia financing, food price